The effect of affect in organizational settings - Ashkanasy, Neal M., 1945-; Zerbe, W. J.; Härtel, Charmine E. J., 1959- (Research on emotion in organizations ;, 2005)
The study of emotion and affect on organizational settings has been steadily gaining momentum for much of the last decade. Important catalysts in this process have been the Emonet e-mail discussion group and the biannual International Conferences on Emotions and Organizational Life. The articles in this volume represent a selection of the best papers presented at the fourth Conference (which was conducted in London, England, in June, 2004), together with invited papers by some of the leading scholars in the field. The theme of the book, the effect of affect in organizations, was chosen to capture the centrality of emotion and affect in everyday organizational life.The opening chapter, co-authored by Howard Weiss, one of the inventors of Affective Events Theory (AET), sets the scene. At the heart of AET is the idea that organizational members experience daily hassles and uplifts that are reflected in their attitudes and behaviours. Following chapters flesh out the way that AET can be applied, covering a variety of constructs that relate to organizational life, including emotional intelligence, motivation, employee monitoring of web access, and emotional regulation. Other chapters deal with other aspects of emotion in organizations, such as loneliness, leader-member relationships in teams, organizational justice, negative behaviour, creativity, and organizational reactions to crisis situations. In the final chapter, Rob Briner and his colleagues round out the theme in a critical account of emotion in organizations.